Scope of coverage of medical genetics and genomics in pre‐clerkship programs of Canadian faculties of medicine: A curriculum analysis. Issue 1 (27th September 2022) - Ouellet, Jade; Lapointe, Julie; Raîche, Camille; Guerin, Andrea; Helal, Shaimaa; Fitzpatrick, Jennifer; Dorval, Michel; Nabi, Hermann
Abstract: We appraised the scope of medical genetics and genomics concepts covered in the pre‐clerkship programs of Canadian faculties of medicine through an analysis of course objectives. All course objectives linked to medical genetics and genomics in pre‐clerkship programs of Canadian faculties of medicine were compiled. From this, the fraction of objectives dedicated to medical genetics and genomics was calculated. Course objectives were also categorized according to a curriculum and a competency classification. Of the 17 Canadian faculties of medicine, the complete set of course syllabi (5 faculties) or the listing of learning objectives (4 faculties) were obtained and reviewed. The fraction of learning objectives dedicated to medical genetics and genomics varied between 0.65% and 5.05%. From the objectives classification, "foundational knowledge" was most frequently covered (64% of the compiled objectives), while topics such as: "ethics and professionalism, " "communicate genetics information, " and "obtain specialist help" were covered by less than 5%. Coverage of medical genetics and genomics in pre‐clerkship programs of Canadian faculties of medicine appears to be low. Genetics and genomics are playing a rapidly expanding role in healthcare and clinical practice and educational programs should consider this new reality.